(untitled) (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract Palm is one of the commodities from the plantation sub-sector that is largely planted by farmers in Bengkulu Province. Plantation areas and production of palm oil keep increasing year by year in Bengkulu, this shows that farmer interest in planting palm is quite high moreover, it is considered a profitable commodity among farmers. This study aims to (1) get to know the development of plantation areas and the productivity of palm oil in Bengkulu year by year (2) get know the effect of plantation areas and productivity of palm towards Plantation PDRB subsector in Bengkulu. This study used a quantitative method. By characteristic this study is statistic descriptive. The data used in this study is secondary data. Analysis was done by using trend and multiple linear regression. The study result shows that PDRB development, plantation area, and production of palm oil from 2009 to 2019 tend to increase. Plantation area and production of palm oil together affect Plantation PDBR Sub sector significantly but have no effect partially on the Plantation PDBR Subsector. Keywords; Palm; Plantation Area; PDRB; Production.